Chitosan oligosaccharide and Enteromorpha prolifera polysaccharides as additives affect the bacterial community and optimize the compost performance - Xingsheng Yin; Shutong Chen; Guangcai Shen; Guangfu Zhang; Guangyun Meng; Siman Gao; Hui Yao; Hui Yao; Xiangwei You; Xiangwei You; Yiqiang Li; Yiqiang Li (Frontiers in Sustainable Food Systems, 2025)
The yield of agricultural wastes is increasing year by year, and composting is a common and effective strategy. However, the influence of marine-derived carbohydrates such as chitosan oligosaccharide (COS) and Enteromorpha prolifera polysaccharides (EPP)—on composting efficiency and microbial dynamics remains poorly understood. Here, we conducted composting experiments using agricultural wastes (cow manure, rice husks, and tomato residues) as substrates, and systematically evaluated the effects of chitosan oligosaccharide (COS) and Enteromorpha prolifera polysaccharides (EPP) supplementation through physicochemical analysis and high-throughput sequencing. These additives not only advanced the thermophilic phase and facilitated compost maturation but also reshaped the composition of the bacterial community in compost piles. By providing suitable microenvironments, the carbohydrates-containing group increased the abundance of thermophilic bacteria such as Ureibacillus, Geobacillus, and Ammoniibacillus, facilitating the degradation and utilization of organic matter. During which, the organic matters loss rates of COS and EPP were 26.61 and 12.66% higher than CK, respectively. By increasing the abundance of Cellvibrio and Flavobacterium in the cooling phase, carbohydrates-containing additives are expected to promote the conversion of recalcitrant lignocellulosic fibers. Additionally, PICRUSt 2 predictions revealed that carbohydrates addition increased the gene abundance related to amino carbohydrates and nucleotide carbohydrates metabolism, fructose and mannose metabolism, galactose metabolism, and butanoate metabolism in the initial and thermophilic phases, thereby facilitating carbohydrate metabolism. In summary, the addition of carbohydrates-containing additives enhanced the maturity and fertility of compost products and exerted significant regulatory effects on the composition and function of the bacterial community during composting.